2016
DOI: 10.5114/aoms.2016.62908
|View full text |Cite
|
Sign up to set email alerts
|

Serum pregnancy-associated plasma protein A levels in the first, second and third trimester of pregnancy: relation to newborn anthropometric parameters and maternal tobacco smoking

Abstract: IntroductionThe purpose of this study was to evaluate the associations of the first, second and third trimester serum pregnancy-associated plasma protein A (PAPP-A) concentrations with neonatal anthropometric parameters. The effect of tobacco smoking during pregnancy on PAPP-A level was also studied.Material and methodsOne hundred and fifty healthy pregnant women were divided into smoking and tobacco-abstinent groups. Serum PAPP-A level was measured with the KRYPTOR rapid random-access immunoassay analyzer. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Thus, the multiple of median (MoM) is a conventional measurement unit that reflects how far the value of a measured parameter (NT or biochemical markers) is from the median value expected for the same gestational age. Because studies showed that some other factors (behavioral or diseases) influence the median value, it is obvious that it is necessary to correct the MoM according to the presence of these factors [4][5][6][7]. So, the corrected multiple of median (MoMc) represents the MoM value adjusted for the presence of interfering factors (mode of conception, presence of diabetes, smoker status, ethnicity, etc).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the multiple of median (MoM) is a conventional measurement unit that reflects how far the value of a measured parameter (NT or biochemical markers) is from the median value expected for the same gestational age. Because studies showed that some other factors (behavioral or diseases) influence the median value, it is obvious that it is necessary to correct the MoM according to the presence of these factors [4][5][6][7]. So, the corrected multiple of median (MoMc) represents the MoM value adjusted for the presence of interfering factors (mode of conception, presence of diabetes, smoker status, ethnicity, etc).…”
Section: Resultsmentioning
confidence: 99%
“…The deviation of a measured value from the median is expressed in multiple of medians (MoM) and is used to calculate a relative risk for aneuploidy. Because it was proved that other parameters (mode of conceiving, smoking, ethnicity, diabetes, etc) interfere with the level of biochemical markers, it is mandatory to correct the MoM according to mentioned parameters [4][5][6][7]. Thus a corrected MoM (MoMc) is calculated for each biochemical marker considering interfering parameters.…”
mentioning
confidence: 99%
“…The birthweight of children born to active smokers during pregnancy has been es-timated to be 150-250 g lower as compared to pregnant non-smokers. Also, the risk for LBW has been reported [20][21][22][23]. The correlation between active maternal smoking and neonatal birthweight depends on the number of cigarettes a day and is visible even for the lowest amount of tobacco in active smokers [6,24].…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, such an effect is also observed in pregnant women who smoke [4,5]. Since some of blood biochemical parameters influenced by inhalation of chemical compounds released by smoking are used to assess the risk of fetal aneuploidy, it is imperative to quantify the degree of alteration and to develop algorithms to counterbalance this effect [6][7][8][9].…”
mentioning
confidence: 99%
“…Since the MoM value directly contributes to the evaluation of the risk, any alteration of values by behavioral, environmental or morphologic factors could negatively influence the accuracy of the screening test [6][7][8][9]. As a result, mathematical strategies were developed to correct the influence of these disturbing factors.…”
mentioning
confidence: 99%